Rikkunshito for Preventing Chemotherapy-Induced Nausea and Vomiting in Lung Cancer Patients: Results from 2 Prospective, Randomized Phase 2 Trials - Toshiyuki Harada; Toraji Amano; Tomoo Ikari; Kei Takamura; Takahiro Ogi; Toshiaki Fujikane; Yuka Fujita; Kageaki Taima; Hisashi Tanaka; Takaaki Sasaki; Shunsuke Okumura; Shunichi Sugawara; et al. (Frontiers Media S.A., 2018)
The herbal medicine rikkunshito has the potential to improve chemotherapy-induced nausea and vomiting (CINV) by stimulating ghrelin secretion. We aimed to evaluate the efficacy and safety of rikkunshito in preventing CINV for patients with lung cancer. Two separate prospective, randomized, phase II parallel design studies were conducted in patients with lung cancer. Fifty-eight and sixty-two patients scheduled to receive highly emetogenic chemotherapy (HEC) and moderately emetogenic chemotherapy (MEC), respectively, were randomized 1:1 to receive either standard antiemetic therapy in accordance with international guidelines (S group) or standard antiemetic therapy plus oral rikkunshito (R group). The primary endpoint was overall complete response (CR)-that is, no emesis and rescue medication in the first 120 h post-chemotherapy. Secondary endpoints included CR in the acute (0-24 h) and delayed (>24-120 h) phases and safety. Fifty-seven patients (S group, 28; R group, 29) receiving HEC and sixty-two patients (S group, 30; R group, 32) receiving MEC with comparable characteristics were evaluated. The CR rates were similar across the S and R groups for the HEC study in the overall (67.9% vs. 62.1%), acute (96.4% vs. 89.6%), and delayed (67.9% vs. 62.1%) phases, respectively, and for the MEC study in the overall (83.3% vs. 84.4%), acute (100% vs. 100%), and delayed (83.3% vs. 84.4%) phases, respectively. No severe adverse events were observed. Although rikkunshito was well tolerated, it did not demonstrate an additional preventative effect against CINV in lung cancer patients receiving HEC or MEC.Clinical Trial Registry Information: This study is registered with the University Hospital Medical Information Network (UMIN) Clinical Trial Registry1, identification numbers UMIN 000014239 and UMIN 000014240.